Bonding of monocarboxylic acids, monophenols and nonpolar compounds onto goethite. (January 2019) - Yu, Chenglong; Devlin, J.F.; Bi, Erping
Abstract: Adsorption of a diverse set of chemicals onto goethite was evaluated by column chromatography. The pH of the effluents was 4.7–5.2. Van der Waals forces dominate the exothermic adsorption of 8 nonpolar compounds (e.g., PAHs and chlorobenzenes). H-bonding is responsible for the adsorption of 32 monocarboxylic acids (i.e., benzoic acids, naphthoic acids and acidic pharmaceuticals) and their adsorption tends to be endothermic. Steric effects significantly decreased the bonding of monocarboxylic acids with ortho-substitutions. Exothermic adsorption of 10 monophenols is controlled by weak H-bonding. Bonding of these 50 solutes onto goethite is totally reversible. In contrast, inner-sphere complexation of phthalic acid and chlortetracycline with goethite occurred according to their low desorption ratio (1.1%–54.4%). Polyparameter linear free energy relationship (PP-LFER) models were established to provide acceptable fitting results of the goethite-solute distribution coefficients (RMSE = 0.32 and 0.30 at 25 °C and 5 °C, respectively). It is worthy to note that steric effects must be considered to get a better prediction for compounds with ortho-substitutions. Graphical abstract: Image 1 Highlights: Adsorption of 50 investigated compounds onto goethite was reversible. H-bonding of monocarboxylic acids was endothermic. Weak adsorption of monophenols and nonpolar compounds was exothermic. Distribution coefficients ( K d ) were fitted by pp-LFER models.